EFFECTIVENESS OF CHILD MARRIAGE PREVENTION POLICY: A LEGAL–SOCIOLOGICAL STUDY IN KAJORAN, MAGELANG - M. Khoirur , Rofiq; Alfian Qodri, Azizi; Mustafakama , Waeduereh; Miss Nipatimoh , Phudaro (UNIVERSITAS NAHDLATUL ULAMA SUNAN GIRI, 2025)
Child marriage is a national issue that negatively affects the formation of quality families. Prevention efforts remain suboptimal, especially in regions with high prevalence, such as Magelang. This study examines the phenomenon of child marriage and analyzes prevention efforts by stakeholders from a legal effectiveness perspective. Using a qualitative field research design with legal and sociological approaches, data were obtained from parents, stakeholders, and children, then analyzed through data reduction, display, and conclusion drawing. The findings show two main results. First, child marriage in Kajoran, Magelang, is driven by (1) a permissive community mindset, (2) low awareness of parents and children due to limited education, and (3) pregnancy or premarital sexual relations. Second, prevention has been ineffective due to: (1) legal factors—laws still permit marriage dispensation, lack sanctions, and are poorly socialized; (2) weak law enforcement; (3) limited facilities, funding, and advocacy staff; (4) low community synergy; and (5) cultural dichotomy between religious and state norms. This study is limited to one subregion of Magelang, indicating the need for broader research to develop a more integrative and effective strategy for preventing child marriage.